Pengembangan Video Animasi Melalui CapCut Berbasis Model Pembelajaran Metakognisi Kolaboratif pada Konten Fenomena Pertumbuhan untuk Meningkatkan Literasi Matematika - Maharani, Rizqona; Marsigit, Marsigit; Wijaya, Ariyadi; Muqoddaroh, Fadillatul (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The research was conducted to improve mathematical literacy skills in the content of the growth phenomenon in class VIII C MTs Miftahul Huda through the development of learning videos based on the collaborative metacognition learning model assisted by CapCut. The research method used is the Research and Development Plomp model through three phases, namely preliminary analysis, prototyping, and assessment. Preliminary analysis produces the need for packaging mathematics learning that can invite students to understand mathematics material easily and solve contextual problems appropriately, so that students' mathematical literacy skills can be improved. Prototyping is carried out by designing a learning video that contains a video opening, problem presentation, problem solving, mathematical concept discovery, and video closing. The assessment was carried out by means of feasibility tests, practicality tests, and learning video effectiveness tests. The results of the video feasibility test from media experts were 0.97 and material experts were 0.97 which stated that they were very valid (feasible). Students rated the videos as very easy to use, useful, engaging, and encouraged metacognitive (practical) activities. Students' mathematical literacy increased in the medium category after using learning videos based on the collaborative metacognition learning model. Students need to get used to building mathematical concepts through contextual problem-solving even though their application takes a relatively long time. On this basis, advanced researchers need to consider the advantages of online learning that provide students with learning flexibility in building their mathematical understanding.